2023
DOI: 10.3390/nano13030521
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Cellulosic Natural Rubber and Silver Nanoparticle Films with Superior Chemical Resistance and Antibacterial Properties

Abstract: Composite films of natural rubber/cellulose fiber/silver nanoparticle were synthesized in a green route via the latex solution process. Hybrid cellulose filler containing carboxymethyl cellulose and cellulose microfibers was used to facilitate facile and fast preparation and to improve mechanical strength to the composites, respectively. All the composites possessed a high tensile strength of ~120 MPa, a high heat resistance of nearly 300 °C, and more than 20% biodegradability in soil in two weeks. Chemical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Among the BC-Ag composites, the highest degree of crystallinity was observed in BC-Ag(Ascorbic), while BC-Ag(Chitosan) showed the lowest degree of crystallinity. Except for BC-Ag(Ascorbic), the incorporation of AgNPs resulted in a slight reduction in the crystallinity of the composites, which could be due to silver interfering with hydrogen bonds within the BC matrix [ 43 ], while chitosan-reduced composites exhibited a significant reduction of crystallinity. The interaction of chitosan molecules with cellulose fibrils might play a significant role in this effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the BC-Ag composites, the highest degree of crystallinity was observed in BC-Ag(Ascorbic), while BC-Ag(Chitosan) showed the lowest degree of crystallinity. Except for BC-Ag(Ascorbic), the incorporation of AgNPs resulted in a slight reduction in the crystallinity of the composites, which could be due to silver interfering with hydrogen bonds within the BC matrix [ 43 ], while chitosan-reduced composites exhibited a significant reduction of crystallinity. The interaction of chitosan molecules with cellulose fibrils might play a significant role in this effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the findings suggest that the antimicrobial effect of BC-Ag composites was not significantly influenced by the method of Ag reduction under the conditions in this study. However, it was previously reported that smaller AgNPs tended to exhibit higher antibacterial activity than larger AgNPs [ 43 ], due to the higher total surface area of the nanoparticles [ 52 ]. Silver particles were shown to strongly adhere to BC, preventing the leakage of AgNPs from the film [ 22 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of silver nanoparticles resulted in a slight reduction in the tensile strength, crystallinity and water absorption capacity of the composite, but the cellulose microfiber reinforcement maintained these properties at a good level. The composites showed heat resistance and biodegradability [59]. These recent studies demonstrate the continued interest in studying the drying behavior of different types of natural rubber and the effects of additives on this process [60].…”
Section: Various Grades Of Natural Rubber Studied For Drying Processmentioning
confidence: 98%
“…Several findings support the development of BC composites for targeted biomedical applications, particularly as antimicrobial wound dressings. The development of BCbased composites incorporating bactericidal nanoparticles like Se [142], Cu [143], Ag [144], ZnO [145], Au [146], and TiO 2 [138] have been extensively researched. Nevertheless, the potential toxicity of these nanoparticles to healthy mammalian cells, resulting from the production of reactive oxygen species, cannot be overlooked despite their antibacterial properties [147,148].…”
Section: Medical Applicationmentioning
confidence: 99%